Muslim scholars’ contribution in hadith authentication - Khan, Israr Ahmad (International Islamic University Malaysia, 2011)
During and after the caliphate of the third Caliph, ‘UthmÉn ibn ‘AffÉn people from different backgrounds and persuasions with criminal mentality tried to corrupt the hadith of the Prophet Muhammad (s.a.w.). Muslim scholars, on the other hand, did not remain silent spectators of the alarming situation; they rose to the occasion and did all that they could to preserve the authenticity and sanctity of sayings of the Prophet (s.a.w.). This preservation and authentication were ensured from both angles, chain of the reporters, and text of the report. This paper represents a humble attempt to introduce contributions of some scholars in the part as well as today towards authentication of hadith.